2018
DOI: 10.5603/fm.a2017.0087
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of prevalence of dental anomalies by using digital panoramic radiographs

Abstract: Anomalies of tooth position were the most common type of dental anomalies and structure anomalies were the least common in this Turkish po-pulation. The frequency and type of dental anomalies vary within and between populations, confirming the role of racial factors in the prevalence of dental ano-malies. Digital panoramic radiography is a very useful method for the detection of dental anomalies. (Folia Morphol 2018; 77, 2: 323-328).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
5
34

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 16 publications
3
58
5
34
Order By: Relevance
“…Contrary to the high prevalence of hypodontia, supernumerary teeth are less frequently found in healthy individuals (0.5-3.8%). The prevalence of supernumerary teeth in our sample was 4.4%, slightly higher than in recent studies [24,25,26]. The etiological pattern of sex distribution in association with supernumerary teeth is the opposite of hypodontia [1].…”
Section: Abnormalities Of Tooth Numbercontrasting
confidence: 69%
“…Contrary to the high prevalence of hypodontia, supernumerary teeth are less frequently found in healthy individuals (0.5-3.8%). The prevalence of supernumerary teeth in our sample was 4.4%, slightly higher than in recent studies [24,25,26]. The etiological pattern of sex distribution in association with supernumerary teeth is the opposite of hypodontia [1].…”
Section: Abnormalities Of Tooth Numbercontrasting
confidence: 69%
“…Törenek A gırman, Ça glayan, & Bilge, 2018;Jeong, Kim, Song, Sung, & Kim, 2015;Patil, Doni, Kaswan, & Rahman, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Goncalves-Filho et al [17] To assess the prevalence of dental anomalies in the Pará population in Brazil.…”
Section: Patients Aged Betweenmentioning
confidence: 99%
“…Studies on the prevalence of dilaceration in individual dental groups showed the occurrence of this disorder within the central upper incisors within the range of 0.2-1.2% [7,9,11,12]. In studies on the prevalence of dental anomalies, apart from taurodontism, impacted teeth, hypodontia and supernumerary teeth, dilaceration was one of the most common dental defects and constituted between 1.4% and 46.71% of all dental anomalies [13][14][15][16][17][18][19][20][21][22]. Dilaceration was more frequently observed in maxillary teeth than in mandibular teeth [9,11,23].…”
Section: Introductionmentioning
confidence: 99%